Lactobacillus improves meat quality in Sunit sheep by affecting mitochondrial biogenesis through the AMPK pathway - Wang, Chenlei; Yan, Xinlei; Bai, Yanping; Sun, Lina; Zhao, Lihua; Jin, Ye; Su, Lin (Frontiers in Nutrition, 2022)
Sunit sheep are famous for their high meat quality, but the meat quality of them has declined due to the change in feeding methods. Lactobacillus has a variety of probiotic effects and is widely used in animal diets to optimize meat quality. This study aimed to investigate the effect of dietary supplementation with different levels of Lactobacillus on meat quality. A total of 24 3-month-old Sunit sheep with an average body weight of 19.03 ± 3.67 kg were randomly divided into control (C), 1% (L1), 2% (L2), and 3% Lactobacillus groups (L3), with 6 sheep in each group. Myofiber characteristics, meat quality, and metabolic enzyme activity were detected. Moreover, the regulatory mechanism of Lactobacillus on meat quality was explored by using Western blotting and real-time Quantitative polymerase chain reaction (RT-qPCR). The results showed that dietary addition of Lactobacillus decreased LDH activity in the Biceps femoris of Sunit sheep (P < 0.05). Compared to the other groups, the 1% Lactobacillus group showed the conversion of myofibers from the glycolytic to the oxidative type, and the increasing b* values (P < 0.05), decreasing shear force and cooking loss of meat (P < 0.05) and the relative gene and protein expression levels of AMPK, PGC-1α, NRF1, TFAM, and COX IV (P < 0.05) in the Biceps femoris were also increased in the 1% Lactobacillus group. Therefore, the addition of Lactobacillus to the diet of Sunit sheep could regulate the AMPK signaling pathway to promote myofiber type conversion, which improves meat quality. This study provided a theoretical and data basis for improving the meat quality of sheep and supplied a novel way of applying Lactobacillus.